Effect of Lanthanum Carbonate on All-Cause Mortality in Patients Receiving Maintenance Hemodialysis: a Meta-Analysis of Randomized Controlled Trials - Fang Wang; Xiangxue Lu; Jingli Zhang; Ruifang Xiong; Han Li; Shixiang Wang (Karger Publishers, 2018)
Background/Aims: Hyperphosphatemia is common in patients on hemodialysis. The efficacy of lanthanum carbonate (LC) in the treatment of hyperphosphatemia in these patients remains controversial. The objective of this meta-analysis was to evaluate the effect of LC on all-cause mortality in patients on maintenance hemodialysis. Methods: We electronically searched the PubMed, EMBASE, and Cochrane Library databases for all randomized controlled trials (RCTs) comparing LC with other phosphate binders used in adult hemodialysis patients, including calcium carbonate, calcium acetate, and sevelamer. Results: Nine RCTs involving 2813 patients were suitable for inclusion. Our results showed that all-cause mortality was significantly lower in patients who received LC than in those who received standard therapy (odds ratio [OR]: 0.45, 95% confidence interval [CI]: 0.32-0.63, P<0.00001). Compared with the controls, patients who received LC had significantly lower serum calcium and higher serum intact parathyroid hormone levels. However, there was no significant difference between the groups in the cardiovascular event rate (OR: 0.58, 95% CI: 0.31-1.06, P=0.07) or in serum phosphorus levels. Conclusion: Compared with standard therapy, LC reduced all-cause mortality in patients on hemodialysis but did not decrease the risk of cardiovascular events. The decrease in serum phosphorus level was similar between LC and the other phosphate binders, but the risk of hypercalcemia was lower in patients who received LC.